The Perinatal Effects of Lithium Carbonate on Hypothalamic-Pituitary-Gonadal in Adult Female Wistar Rats - ebrahim hosseini; zahra dalaeli (Fasa University of Medical Sciences, 2015)
Background & Objectives: Lithium is the metal used in bipolar disorder treatment.  As for the prevalence of the disorder infertility (childbearing) age and the use of lithium, this study aimed at studying the effects of drugs on histological changes, and the ovarian function in the first generation of adult female offspring was performed. Materials & Methods: In this experimental study, 40 pregnant mice were divided into 5 groups of 8, including a control group. The control and the experimental groups consumed three dosages of 60, 120, and 180 mg/kg lithium carbonate for 21 days. At the end of the sixth week postpartum, 10 mice were randomly selected from the offspring in each group and were then phlebotomized in order to measure the estrogen, progesterone, FSH, and LH hormones. Their ovaries were removed, and after preparing and staining the tissue sections, the types of follicles were counted. The results were analyzed using SPSS-18 software and ANOVA and Tukey's tests. Finally, the significant difference of data P  0/05 was considered. Results: The results showed that lithium caused a significant increase in the number of atresia follicles and a reduction in primordial, primary, and secondary follicles, graph and corpus luteum, estrogen, progesterone, FSH, and LH hormones in the first generation offspring at P&le 0/05. Conclusion: Using lithium during pregnancy led to an increase in the atresia follicle and a decrease in other follicles in the first generation offspring moreover, the sex hormone levels also decreased probably due to the reduction in the follicle and corpus luteum.